Study the anticancer mechanism of the promissing compound 2B2D by using microarray technique - Do, Thao Thi; Do, Phuong Thi; Nguyen, Trang Thi; Nguyen, Nga Thi; Huang, Ying Chi (Vietnam Journal of Science and Technology, 2017)
Being a modern technique with the ability of studying, discovering, probing and analyzing the  expression  of  thousands  genes,  even  the  whole  genome  in  the  only  one  experiment, microarray  proved  to  be  a  powerful  tool  for  cancer  research  especially  at  molecular  level. Employing  the  potential  anticancer  compound  1-(5,7-dimetoxy-2,2-dimetyl-2H-cromen-8-yl)-but-2-en-1-on  (2B2D  in  short) and LU-1,  the human  lung cancer cells as  research objects, we successfully  hybridized  the  cy3/5  incorporated  cDNA  with  Phalanx  HOV5  microarray.  The results  showed  742  genes  that  got  effected with  equal  or  over  two  folds  change  under  2B2D treatment.  Among  -  those,  386  genes  were  up-regulated  while  the  other  356  were  down-regulated. The Nuclear  factor  (erythroid-derived  2,  regulatory  factor X  domain  containing  1, fibroblast  growth  factor  receptor  3  (achondroplasia,  thanatophoric  dwarfism)  and  E2F transcription factor 8 genes were the most stimulated by our compound. The genes that named as Solute carrier  family 7  (cationic amino acid  transporter,  system) member 11,  kelch-like 24 and Hypothetical LOC344887 were the most down in action.